Clonal architecture of CXCR4 WHIM‐like mutations in Waldenström Macroglobulinaemia. (13th December 2015) - Xu, Lian; Hunter, Zachary R.; Tsakmaklis, Nicholas; Cao, Yang; Yang, Guang; Chen, Jie; Liu, Xia; Kanan, Sandra; Castillo, Jorge J.; Tai, Yu‐Tzu; Zehnder, James L.; Brown, Jennifer R.; et al.
Summary: CXCR4 WHIM somatic mutations are distinctive to Waldenström Macroglobulinaemia (WM), and impact disease presentation and treatment outcome. The clonal architecture of CXCR4 WHIM mutations remains to be delineated. We developed highly sensitive allele‐specific polymerase chain reaction (AS‐PCR) assays for detecting the most common CXCR4 WHIM mutations ( CXCR4 S338X C>A and C>G ) in WM. The AS‐PCR assays detected CXCR4 S338X mutations in WM and IgM monoclonal gammopathy of unknown significance (MGUS) patients not revealed by Sanger sequencing. By combined AS‐PCR and Sanger sequencing, CXCR4 WHIM mutations were identified in 44/102 (43%), 21/62 (34%), 2/12 (17%) and 1/20 (5%) untreated WM, previously treated WM, IgM MGUS and marginal zone lymphoma patients, respectively, but no chronic lymphocytic leukaemia, multiple myeloma, non‐IgM MGUS patients or healthy donors. Cancer cell fraction analysis in WM and IgM MGUS patients showed CXCR4 S338X mutations were primarily subclonal, with highly variable clonal distribution (median 35·1%, range 1·2–97·5%). Combined AS‐PCR and Sanger sequencing revealed multiple CXCR4 WHIM mutations in many individual WM patients, including homozygous and compound heterozygous mutations validated by deep RNA sequencing. The findings show that CXCR4 WHIM mutations are more common in WM than previously revealed, and are primarily subclonal, supporting their acquisition after MYD88 L265P in WM oncogenesis. The presence of multiple CXCR4 WHIM mutations within individual WM patients may be indicative of targeted CXCR4 genomic instability.